Methods to Decrease Carbon Emission at the University of Szeged - László Gyarmati (Journal of Sustainability Perspectives, 2021)
The implementation of innovations and technologies to decrease carbon emission is one of the main priorities that the University of Szeged is striving to achieve. Although, effective investments cannot be carried out without proper measurement systems in energy management and carbon emission monitoring. Understanding the importance of proper measurement, the University of Szeged has decided to calculate the whole carbon footprint of one of its main buildings, namely, the Study and Information Centre with the help of KÖVET association. The carbon evaluation uses data of 2019 and contains the direct and indirect carbon emission of building management, and of its employees’ and visitors’. This calculation will be the basis of further carbon reduction investments, protocols and events held for shaping the visitors’ and employees’ consciousness. In parallel with the evaluation, the University of Szeged has made some huge steps to decrease carbon emission factors. For instance, a newly installed visitor monitoring system regulates the electricity usage of ventilation in the most used areas of the Study and Information Centre based on the actual number of visitors present in the building. Furthermore, from April 2020, five electric cars substitute the most driven cars of the University in urban areas, rapidly decreasing the direct carbon emission in the city.